Penerapan Algoritma Naive Bayes Untuk Sistem Klasifikasi Status Gizi Bayi Balita - Mohamad Ilyas Abas; Rizal Lamusu; Widya Eka Pranata; Syahrial Syahrial; Irawan Ibrahim; Wahyudin Hasyim; Verliana Kiayi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Infants and toddlers are in a critical period of rapid growth and development, often referred to as the